Genetic Diversity of Gazelles (Gazella marica and Gazella gazella) in Southeast Turkey: A Special Emphasis on Ongoing Conservation Studies of Gazella marica in Turkey - (:unkn) unknown (My University, 2019)
Objective: The genetic diversity parameters for gazelle populations sampled in Turkey were estimated to assess the effectsof captive breeding on the populations’ gene pools and effective population sizes.Materials and Methods: Four individuals from a recently discovered Gazella gazella population in Hatay and two captivegazelle populations were sampled (the Kızılkuyu State Farm (n=48) and the Erikçe State Farm (n=25)) and analyzed usingnuclear DNA, mtDNA and Y-chromosome markers.Results: The mtDNA cyt-b partial sequence analysis assigned the Erikçe and Kızılkuyu samples to Gazella marica. Thestructure analysis differentiated significantly between them, and revealed samples originating from wild population. Both,the Y-chromosome INRA126 locus sequences of Gazella gazella and Gazella marica males and the mtDNA partial cyt-b regionRFLP analysis from all the samples distinguished the two gazelle species from each other. Based on microsatellites, theestimated effective population sizes were 9.7, 8.9 and 6.4 for the Kızılkuyu, Erikçe and Hatay populations, respectively. Whenthe Kızılkuyu and Erikçe populations (where severe inbreeding depressions seems to be occurring already) were pooled, theestimated Ne was 24.5. All these estimates were too small for the sustainability of either individual or pooled populations inthe wild or even in captivity.Conclusion: The markers used in the study provided information on two of the gazelle species (Gazella marica, and Gazellagazella): their species identity, degree of divergences, effective population sizes and the presence of admixture within thepopulations. These results turned out to be invaluable in terms of their contribution to future studies for the conservation ofthese species.
Keywords: Biyoloji